ショウワキチ ト ドームフジキチ ニ オケル エアロゾル リュウケイ ブンプ ノ ツウネン カンソク - 林, 政彦; ハヤシ, マサヒコ; 松本, 易典; マツモト, ヤスノリ; 平沢, 尚彦; ヒラサワ, ナオヒコ; 山内, 恭; ヤマノウチ, タカシ; 岩坂, 泰信; イワサカ, ヤスノブ; Hayashi, Masahiko; Matsumoto, Yasunori; et al. (2010)
P(論文) 1997年2月～1998年1月に,昭和基地(69゜00′S,39゜35′E,15 m a.s.l.)及びドームふじ観測拠点(77゜19′S,39゜42′E,3810 m a.s.l.)において,直径0.003-5 μmのエアロゾル粒径分布の変動の観測を行った.両基地において小エイトケンモード(直径0.05 μm以下),大エイトケンモード(直径0.05-0.3 μm),大粒子・粗大粒子モード(直径0.3 μm以上)の3つのモードが認められた.小エイトケンモードおよび大エイトケンモードは,夏に高濃度,冬に低濃度となり,一方,大粒子・巨大粒子モードは夏に低濃度,冬に高濃度となった.1～数日の時間スケールの全粒径にわたる急増,急減現象が両基地で冬季に見られた.ドームふじ観測拠点では春季に小エイトケン粒子のみの急増も見られた.ドームふじ観測拠点においてこれらの現象が起こる気象条件は,昭和基地における類似の現象が起こる時の気象条件とは異なっていた. Simultaneous observations of the aerosol size distribution for diameters of 0.003-5.0 μm were performed at Syowa Station (69゜00′S, 39゜35′E, 15 m a.s.l.) and Dome Fuji Station (77゜19′S, 39゜42′E, 3810 m a.s.l.) in Antarctica from February 1997 to January 1998. Size distributions show composites of a small-Aitken mode (less than 0.05 μm in diameter), a large-Aitken mode (0.05-0.3 μm in diameter), and a large giant particle mode (larger than 0.3 μm in diameter). Concentrations of small and large Aitken modes were high in summer and low in winter. On the other hand, concentrations of large giant particle mode were low in summer and high in winter. The high and or low concentration events for one or a few days in whole size range were observed especially in winter. High concentration events in small Aitken mode with the low concentrations in diameter of 0.07-5.0 μm were also observed at Dome Fuji Station in spring. Meteorological conditions during the events at Dome Fuji Station were different from those at at Syowa station. departmental bulletin paper